Student Creativity Boosting with Innovative Digital Activities to Enhance Study Course Quality - Rudzinska, Ieva; Pop, Anisoara; Dredetianu, Mirela (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article aims to introduce some digital activities for ESP (English for Specific Purposes) courses and show the effect of their introduction on the quality of study process in an ESP course and on its results. With the help of ESP course quality evaluation model (Rudzinska, 2011) ESP course quality is evaluated along the following criteria: study course clarity, adequacy, cooperation, individual work, variety, and deep approach. Quantitative and qualitative research methods are used to investigate the improvement of study process quality due to the introduction of digital tools. The base of the research are the students of a Latvian higher education institution (HEI) (Institution A) and a Romanian  HEI (Institution B), who from 2008/2009 to 2011/2012 studied ESP (Business English and Sports English) with the help of such digital tools as Bighugelabs, Piclits, Glogster, Textivate, Freemind and Wikipedia article creation. In Institution B student satisfaction level with the use of digital tools was surveyed through a 5-point Likert scale questionnaire and oral interviews. In Institution A the students freely reflected on their learning experience with the help of the mentioned digital tools. The results in both HEIs show high student satisfaction with the introduction of digital tools: in Institution B slightly satisfied were 15%, moderately satisfied: 10%, very satisfied: 58%, and extremely satisfied: 15% of respondents. Qualitative analysis showed that ESP course quality due to the introduction of digital tools improved in relation to quality criteria, summarized in the mentioned quality evaluation model (clarity, adequacy, cooperation, individual work, variety, and deep approach), as well as in relation to other quality criteria:  accessibility, availability, novelty, variety, creativity, an opportunity to be proud about the results of the work done; the weaknesses were due to lack of accessibility (Internet connection in my village is too slow), lack of creativity (I’m not very creative) and complicated techniques of digital tool application.